Isolation of some of the active constituents from the leaves of morinda citrifolia linn. (Noni). - Grande, Teresa Connie
Phytochemical screening of fresh leaves samples of Morinda citrifolia, Linn. for Alkaloids and Saponins gave negative results. However bioassay results of the crude methanolic extract indicated that the sample has antispasmodic activity., Extraction of seven hundred thirty two grams (732 g.) powdered and air-dried leaves of Morinda citrofolia, Linn with 70 percent Methanol, yielded a dark green concentrate. Thin layer Chromatography (TLC) profile of the crude extract gave nine (9) spots using n-Hexane:Ethyl acetate (2:1) as solvent system and Vanillin Sulfuric solutions as indicators. Isolation of theconstituents responsible for the antispasmodic activity was attempted by subjecting the concentrated crude extract to liquid-liquid extraction using solvents of increasing polarity (n-Hexane, Dichloromethane and Ethyl acetate). All fractions has antispamodic activity but n-Hexane extract gave the highest result. hence, the complexity of hte n-Hexane fraction (F-A) was further reduced using Vacuum liquid Chromatography (VLC). The two fraction, F-A.3 and F-A.5, obtained from Vacuum Liquid Chromatography had very promising Antispamodic Activity. The percent length traveled by charcoal in the mice pretreated with Fractions A.5 (45.56 percent) and A3 (50.62 percent) were both lower than the Positive control, Loperamide (54.14 percent0 and Solvent control, Corn oil (66.51 percent). Thus both had higher antispamodic activities than the positive control. Fraction A.5 was further subjected to Vacuum Liquid Chromatography. TLC profile of the fractions was etermined using n-Hexane:DCM (7:2) as solvent system and UV (254nm) and Vanillin sulfuric solotuins as indicators. And the least complex fraction (F-A.5.4) based on the TLC results, had antispamodic activitycomaparable to Loperamide